AI 2013: Advances in Artificial Intelligence 26th Australian Joint Conference, Dunedin, New Zealand, December 1-6, 2013. Proceedings - Cranefield, Stephen; Nayak, Abhaya C. (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes the refereed proceedings of the 26th Australasian Joint Conference on Artificial Intelligence, AI 2013, held in Dunedin, New Zealand, in December 2013. The 35 revised full papers and 19 revised short papers presented were carefully reviewed and selected from 120 submissions. The papers are organized in topical sections as agents; AI applications; cognitive modelling; computer vision; constraint satisfaction, search and optimisation; evolutionary computation; game playing; knowledge representation and reasoning; machine learning and data mining; natural language processing and information retrieval; planning and scheduling.